Age of onset determines intrinsic functional brain architecture in Friedreich ataxia. Issue 1 (18th December 2019) - Naeije, Gilles; Wens, Vincent; Coquelet, Nicolas; Sjøgård, Martin; Goldman, Serge; Pandolfo, Massimo; De Tiège, Xavier P.
Abstract: Objective: Friedreich ataxia (FRDA) is the commonest hereditary ataxia in Caucasians. Most patients are homozygous for expanded GAA triplet repeats in the first intron of the frataxin ( FXN ) gene, involved in mitochondrial iron metabolism. Here, we used magnetoencephalography (MEG) to characterize the main determinants of FRDA‐related changes in intrinsic functional brain architecture. Methods: Five minutes of MEG signals were recorded at rest from 18 right‐handed FRDA patients (mean age 27 years, 9 females; mean SARA score: 21.4) and matched healthy individuals. The MEG connectome was estimated as resting‐state functional connectivity (rsFC) matrices involving 37 nodes from six major resting state networks and the cerebellum. Source‐level rsFC maps were computed using leakage‐corrected broad‐band (3–40 Hz) envelope correlations. Post hoc median‐split was used to contrast rsFC in FRDA patients with different clinical characteristics. Nonparametric permutations and Spearman rank correlation test were used for statistics. Results: High rank correlation levels were found between rsFC and age of symptoms onset in FRDA mostly between the ventral attention, the default‐mode, and the cerebellar networks; patients with higher rsFC developing symptoms at an older age. Increased rsFC was found in FRDA with later age of symptoms onset compared to healthy subjects. No correlations were found between rsFC and other clinical parameters. Conclusion: Age of symptoms onset is a major determinant of FRDA patients' intrinsic functional brain architecture. Higher rsFC in FRDA patients with later age of symptoms onset supports compensatory mechanisms for FRDA‐related neural network dysfunction and position neuromagnetic rsFC as potential marker of FRDA neural reserve.